A Study on the Mechanism by which Art Education Enhances the Marketing Skills of College Students (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the mechanisms through which art education contributes to the development of college students’ marketing skills. In the era of globalization, marketing requires human resources who are adaptive, creative, communicative, and socially as well as culturally sensitive. Art education is not only oriented toward aesthetic aspects but also emphasizes imagination, expression, and symbolic meaning-making processes that are highly relevant to modern marketing practices. Using a qualitative approach with a descriptive-analytical design, this research explores the relationship between art learning processes and students’ creativity, communication abilities, and social sensitivity. Data were collected through literature review, classroom observations, and analysis of academic documents. The findings reveal that art education encourages students to think divergently, take creative risks, and generate innovative ideas that support marketing strategies. Furthermore, art education strengthens both verbal and nonverbal communication skills, enhances presentation abilities, and expands digital communication literacy. It also fosters empathy, tolerance, and cultural awareness, which are essential for designing inclusive and sustainable marketing strategies. Therefore, integrating art education into marketing curricula not only improves graduates’ competitiveness but also shapes professionals who are creative, communicative, and socially responsible. This study provides theoretical contributions to interdisciplinary education research and practical references for higher education institutions in designing innovative learning strategies.